EQUIVALENT CIRCUIT SIMULATION OF A TWO-DEGREE-OF-FREEDOM ELASTIC COLLISION VIBRATION SYSTEM WITH GAPS - ZHU Xifeng; FU Wenbin; MA Shuo; ZHENG Dong (Jixie qiangdu)
A two-degree-of-freedom collision system with gap and elastic constraint was used as the research object, and the regional distribution and transitions of the periodic motion of the system under low frequency conditions were studied by numerical simulation.It was obtained that with the decrease of excitation frequency, the p/1 periodic motion occurs with grazing bifurcation transitions to （p+1）/1 periodic motion.When the number of collisions was large enough, the Chattering-impact characteristics were presented.Then a circuit model that was completely equivalent to the collision system was established and simulation experiments were carried out.The results show that the results generated by establishing the equivalent circuit are consistent with those generated by numerical simulations, and the equivalent circuit is more efficient in simulation experiments, which can realize fast modal transitions and parameter adjustments，making it more convenient and providing a research method for the study of nonlinear dynamics.